Cultural co-orientation revisited: The case of the South China Morning Post - Wiebrecht, Felix (Global Media and China, 2018)
The freedom of press is one aspect that leaders from the West often criticise about China. As former British colony, Hong Kong has been able to preserve its special status with constitutional rights and liberties that also include the freedom of press. However, in recent years, sentiments of increased influence from Beijing have led to fears that it would curb the freedoms enjoyed by residents of the Special Administrative Region. However, instead of clear unambiguous interferences, Beijing has opted for an indirect approach that is predominantly characterised by the salience of economic considerations in reporting news binding the media outlets closer to the position of Beijing. This article shows that the South China Morning Post has undergone an editorial shift that moves it closer to the position of the Chinese government.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8yMDU5NDM2NDE4Nzc4MzA2